Structural, Magnetic and Electrical Properties of BiFeO3 Nanopowders Prepared by Combustion Process - Robert Xavier1, A.; Catherine Siriya Pushpa2, K.; Srinivas3, J.; Ravich, A.T. (Asian Journal of Chemistry, 2013)
Nanocystalline BiFeO3 powders have been synthesized by means of a quick and solution combustion method using glycine as a fuel. The starting materials were directly mixed and a slurry precursor with high homogeneity was formed due to hygroscopicity of the reactants. The precursors could be ignited at room temperature resulting in dry, loose and voluminous BiFeO3 powders. The structural and morphology of the as-prepared combustion products were investigated by means of X-ray diffraction. The microstructural evolution and the morphological features of the obtained ferrites were studied by scanning electron microscopy. The UV-VIS spectra are also studied. The FT-IR studies of the samples ensure the characteristics absorption bands of ferrites. The vibrational sample magnetometer measurements were carried out on the resultant powders. The AC electrical conductivity has also been studied.